2008
DOI: 10.1103/physrevlett.100.067401
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Intrinsic Radiative Decay Rates of Silicon Nanocrystals at Large Confinement Energies

Abstract: We study ultrafast photoluminescence (PL) dynamics of Si nanocrystals (NCs). The early-time PL spectra (<1 ns), which show strong dependence on NC size, are attributed to emission involving NC quantized states. The PL spectra recorded for long delays (>10 ns) are almost independent of NC size and are likely due to surface-related recombination. Based on instantaneous PL intensities measured 2 ps after excitation, we determine intrinsic radiative rate constants for NCs of different sizes. These constants sharpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
135
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 23 publications
22
135
2
7
Order By: Relevance
“…While many experimental works point toward strong luminescence due to quantum-confined excitons in Si nanostructures fabricated with different methods [8,[11][12][13][14], others suggest that the PL emission arises from highly localized surface states [14][15][16][17]. Godefroo and co-authors, using PL measurements under high magnetic fields, showed that the optical emission of as-crystallized SiO x /SiO 2 superlattices may be related to defects, whereas it becomes entirely originated by excitonic quantum confinement (QC) after H passivation [7].…”
Section: Introductionmentioning
confidence: 99%
“…While many experimental works point toward strong luminescence due to quantum-confined excitons in Si nanostructures fabricated with different methods [8,[11][12][13][14], others suggest that the PL emission arises from highly localized surface states [14][15][16][17]. Godefroo and co-authors, using PL measurements under high magnetic fields, showed that the optical emission of as-crystallized SiO x /SiO 2 superlattices may be related to defects, whereas it becomes entirely originated by excitonic quantum confinement (QC) after H passivation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The redshift of the PL spectrum of PSi by the light-illumination was reported, 28 but its mechanism is still unclear. We consider that the recombination at the surface-related states 31 may be attributed to this type of redshifted PL spectra. The present Ni/PSi composite powders with hydrophilic, superparamagnetic, and stable luminescence properties can be used for biomedical applications such as photodynamic therapy 3 and drug delivery 21 in microfluidic systems.…”
Section: Photoluminescence Properties Of Ni/psi Powdersmentioning
confidence: 99%
“…This emission timescale is much faster than that of ls-scale emissions relating to defects reported in several studies of Sinanocrystals. 5,8 Therefore, the present fast PL components originate from intrinsic states of the individual Si-NDs. The relative intensity ratios of these two PL components as a function of excitation power are shown in Fig.…”
mentioning
confidence: 96%
“…Si nanostructures have extensively been studied owing to their potential applications in future photovoltaics and optoelectronics. [1][2][3][4][5][6][7][8][9][10][11] Si nanostructures with dimensions of less than 10 nm can behave as quantum dots (QDs) due to a three-dimensional quantum confinement effect for carriers. Minibands of carriers will arise from overlapping of the confined wavefunctions in high-density QDs regularly aligned.…”
mentioning
confidence: 99%